America's quarterback : Bart Starr and the rise of the National Football League - Dunnavant, Keith (Thomas Dunne Books, 2011)
Offers insight into the life and career of former football player and coach Bart Starr, discussing his high school years in Montgomery, Alabama, his success as quarterback for the Green Bay Packers, and the family tragedies he faced.